Simulation of Innovative Resonance in the Industrial Regions - Akberdina, Viktoriya Viktorovna; Grebenkin, Anatoliy Viktorovich; Bukhvalov, Nikolay Yuvenalyevich (Economy of Regions, 2015)
The main purpose of the article is to validate the mathematical models describing the innovative response in the industrial regions. The article gives a deep analysis of trends in the development of the Russian industrial regions, puts forward and tests the following hypotheses: the hypothesis of uneven economic development of different types of industrial regions (regions, strengthening its industrial status, new industrial regions and regions of deindustrialization), the hypothesis of the development identity of certain types of industrial regions, the hypothesis of the catalytic role of the state in the dynamics of innovation, the hypothesis of the existence of the resonance innovation in the economic system. The authors propose the innovative resonance methodology, show the conditions for the resonance in the economic system, describe the types of resonant response. The main methods used are: resonance effects, reproductive techniques and methods of economic-mathematical modelling. In the paper, the authors propose a mathematical formalization of the innovative resonance mechanism in the regional industrial system, which includes: a) the development model of investment by industry and reproductive sectors; b) the dynamic diversified (multi-sectoral) model of reproduction; c) the model of the adaptive management of the innovative self-development of regional industrial system; d) the model of the stability of innovation dynamics and extended reproduction. The authors study the innovative response in the industrial regions of Russia. In the context of innovation resonance, the authors examined the functional industrial policies of a typical industrial region and the resonant responses associated with its implementation. The results of the study presented in the paper can be used in the justification of the mechanisms of the regional industrial policy, as well as for the assessment of the regulatory impact of the existing legal acts.